Synthesis of CuO Nano structure via Sol-Gel and Precipitation Chemical Methods - Jabbar, Saja Mohsen (Al-Khwarizmi Engineering Journal, 2017)
CuO nanoparticles were synthesized in two different ways, firstly by precipitation method using copper acetate monohydrate Cu(CO2CH13)2·H2O, glacial acetic acid (CH3COOH) and sodium hydroxide(NaOH), and secondly by sol-gel method using copper chloride(CuCl2), sodium  hydroxide (NaOH) and ethanol (C2H6O). Results of scanning electron microscopy (SEM) showed that different CuO nanostructures (spherical and Reef) can be formed using precipitation and sol- gel process, respectively, at which the particle size was found to be less than 2 µm. X-ray diffraction (XRD)manifested that the pure synthesized powder has no inclusions that may exist during preparations. XRD results showed the particles size of highest peak at 38.9°, was  equal to (15.93nm). In addition, Fourier transform infrared spectroscopy (FT-IR) were used to describe the prepared CuO nanostructures absorption peak at 610 cm-1 which conﬁrms that the synthesized product is a pure CuO and may be attributed to Cu2O infrared active mode.